Phantom of the forest or successful citizen? Analysing how Northern Goshawks (Accipiter gentilis) cope with the urban environment - Manuela Merling de Chapa; Alexandre Courtiol; Marc Engler; Lisa Giese; Christian Rutz; Michael Lakermann; Gerard Müskens; Youri van der Horst; Ronald Zollinger; Hans Wirth; Norbert Kenntner; Oliver Krüger; et al. (Royal Society Open Science, 2020)
By 2040, roughly two-thirds of humanity are expected to live in urban areas. As cities expand, humans irreversibly transform natural ecosystems, creating both opportunities and challenges for wildlife. Here, we investigate how the Northern Goshawk (Accipiter gentilis) is adjusting to urban environments. We measured a variety of behavioural and ecological parameters in three urban and four rural study sites. City life appeared related to all parameters we measured. Urban female goshawks were overall 21.7 (CI95% 5.13–130) times more likely to defend their nestlings from humans than rural females. Urban goshawks were 3.64 (CI95% 2.05–6.66) times more likely to feed on pigeons and had diets exhibiting lower overall species richness and diversity. Urban females laid eggs 12.5 (CI95% 7.12–17.4) days earlier than rural individuals and were 2.22 (CI95% 0.984–4.73) times more likely to produce a brood of more than three nestlings. Nonetheless, urban goshawks suffered more from infections with the parasite Trichomonas gallinae, which was the second most common cause of mortality (14.6%), after collisions with windows (33.1%). In conclusion, although city life is associated with significant risks, goshawks appear to thrive in some urban environments, most likely as a result of high local availability of profitable pigeon prey. We conclude that the Northern Goshawk can be classified as an urban exploiter in parts of its distribution.